Management of Ankyloglossia and Breastfeeding Difficulties in the Newborn: Breastfeeding Sessions, Myofunctional Therapy, and Frenotomy - Elvira Ferrés-Amat; Tomasa Pastor-Vera; Paula Rodríguez-Alessi; Eduard Ferrés-Amat; Javier Mareque-Bueno; Eduard Ferrés-Padró (Case Reports in Pediatrics)
The problems of suction in newborns give rise to multiple consequences for both the mother and the newborn. The objective of this paper is to present a case of ankyloglossia (“tongue-tie”) and the suction problems that were treated by a multidisciplinary team. The subject is a 17-day-old male patient, with ankyloglossia and suction problems during breastfeeding (pain in the breastfeeding mother, poor weight gain, and long breastfeeds). The patient followed the circuit established in our centre between the services of Oral and Maxillofacial Surgery and Breastfeeding and Speech Therapy and Orofacial Rehabilitation (CELERE). The evolution following the breastfeeding sessions, the myofunctional stimulation, and the lingual frenotomy was very favourable, thereby solving the suction problems that the newborn presented. All our patients receive breastfeeding sessions and myofunctional therapy as treatment. We know that a frenotomy is not always necessary and we believe that the stimulation of sucking before and after the surgical intervention is important in order to improve the final result.